(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
A digital rights management (DRM) system designed for digital document protection is presented in this paper. DRM technologies include technologies that can be used to impose direct functionality restrictions on digital content. Technologies can be designed to effectuate the concept of self help such as disabling access to the database or to some portion of the database if the system detects an attempt to engage in some sort of impermissible action, or detects unauthorized files residing on the user’s computer. Digital Rights Management (DRM) involves the description, layering, analysis, valuation, trading and monitoring of the rights over an individual or organization’s assets; both in physical and digital form; and of tangible and intangible value. This paper will discuss some background information on the protection of documents, the various technical measures employed by this DRM system. The technical measures include a variety of tamper-resistance methods, controlled execution techniques, encryption, digital watermarking and other techniques. Concept and limitations and future directions of the technology are made throughout.